"Vital Negotiations": Health Care and Disease Control in colonial South Carolina and Louisiana (KULT_online, 2014)
Concentrating on the fields of health care and disease control, Marion Stange's newly published comparative work Vital Negotiations presents an impressive addition to the studies of North American colonial history. While analyzing which measures of health care and disease control were introduced in French Louisiana and British South Carolina, the study succeeds in shedding more light on local forms and practices of governance in the eighteenth century. In the process, Stange continuously stresses the significance of local conditions and emphasizes the key role of official, semi-official, and non-official agents. As a result, Stange challenges traditional works that accentuate the differences of colonial governance, and concludes that "the differences between the two administrative systems were not as great as might be expected judging from the distinct characters of the French and British colonial empires" (p. 238).